Social Status and Gene Regulation: Conservation and Context Dependence in Primates - Simons, Noah D. (Trends Cogn Sci, 2019)
Current models suggest that low social status affects immune function by increasing inflammation and compromising antiviral defense. While this pattern appears to be somewhat conserved, recent studies argue that the gene regulatory signature of social status also depends on the local environment and the nature of social hierarchies.